Security of Physical Library Materials and Utilisation: A Case Study of National Teachers College Kabale. - Arineitwe, Doreen (Kabale University, 2023)
The purpose of the study was to assess the status of the security of physical library materials and their utilization at National Teachers College Kabale. National Teachers College Library manages wide range of information resources accessible to the students and lecturers to support teaching and learning. The college library faces theft of collection, abuse such as mutilation, defacing of documents. Olabode (2017) observed from interaction with a cross section of library staff that it appears there is a lack of proper collection policy and procedures formulated to support the security of the library collection and the activities involved in the management of security issues in libraries. Many college libraries fail to recognize the vulnerability and security of their collections to loss (Ajegbomogun, 2014). Library collections at NTC Kabale can be threatened not just by theft and vandalism, but also by disasters (e.g., fire or flood) and damage from careless handling or poor environmental conditions. Poor security cannot cope with incessant pressure on the library by students who either steal or mutilate books/ journals without regard for laid down library regulations.